Obligation to Prove Appearer Document Authenticity as Deelneming Claim Exception - BUDIANTO, Agus; SIHOMBING, Jonker; KRISSANTI, Veronica Dini; JAMIN, Silvia; PRAMONO, Rudy; PURWANTO, Agus (Journal of Advanced Research in Law and Economics; Vol 11 No 3 (2020): JARLE Volume XI Issue 3(49) Summer 2020DO - 10.14505/jarle.v11.3(49).08, 2020)
Notary is a public official who provides legal services to the public. Notary's Authorities are regulated in Article 16 paragraph (1) of Law Number 2 of 2014 on Amendment to Law Number 30 of 2004 on Position of Notary. Based on data of Directorate of General Criminal Investigation Metro Jaya in 2014 and 2017, the number of Notaries who were placed as suspects and witnesses of criminal acts and falsification were increased. It was because of the absence of obligation to prove appearer document authenticity as contained in Supreme Court Decree Number 702 K/Sip/1973, September 5, 1973. The research was sociological normative by testing the truth of deelneming criminal exception with secondary data, supported by primary data in the form of interviews, using non-random purposive sampling. Theory of lesser evil made Notary is excluded from deelneming claim in Article 55 of Criminal Code on documents falsification, as long as the Public Notary applies 2015 Law and Ethics Code, and ignores Supreme Court Decree Number 702 K/Sip/1973, September 5, 1973. Further, he continues to conduct his duties within a standard operating procedure for himself and related agencies when proving the documents in the form of minutes. Therefore, this exception principle in falsification is given conditionally. It applies to Notary if he can prove that he has conducted an act to prove appearer documents).